Effects of a Bacillus-Based Probiotic on Sow Performance and on Progeny Growth Performance, Fecal Consistency, and Fecal Microflora - M. B. Menegat; K. M. Gourley; M. B. Braun; J. M. DeRouchey; J. C. Woodworth; J. Bryte; M. D. Tokach; S. S. Dritz; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2018)
The objective of this study was to evaluate the effects of supplementation ofBacillus subtilisC- 3102 on sow performance and fecal microflora and on progeny growth performance, fecal consistency, and fecal microflora. For the sow portion of this study, a total of 29 sows (DNA 241, DNA Genetics, Columbus, NE) and litters were used from d 30 of gestation until weaning (d 19 of lactation). Treatments consisted of providing a control diet (n = 14 sows) or a probiotic diet (n = 15 sows) supplemented withBacillussubtilisC-3102 (Calsporin®, Calpis Co. Ltd., Tokyo, Japan) at 500,000 CFU/g of complete feed in gestation and 1,000,000 CFU/g of complete feed in lactation. For the nursery portion of the study, a total of 358 weaned pigs (DNA 241 × 600, DNA Genetics, Columbus, NE) progeny of the sows on study, were used in a 42-d nursery trial. There were 4 or 5 pigs per pen and 18 or 19 replications per treatment. Treatments were arranged in a 2 × 2 factorial with main effects of sow treatment (control diet vs. probiotic diet) and nursery treatment (control diet vs. probiotic diet). In the nursery probiotic diet, a combination of the probioticBacillus subtilisC-3102 and prebiotics based on beta glucans and mannan oligosaccharides (BacPack ABF™, Quality Technology International, Inc., Elgin, IL) was included at 0.05% of complete feed. Fecal scoring was used to categorize fecal consistency of nursing litters and nursery pens. Fecal samples were collected from sows and piglets for microbial analysis performed by culture method and bacterial quantification. The results demonstrate that sows fed the probiotic diet had a marginally significant (P= 0.056) increase in lactation average daily feed intake (ADFI), consuming on average 0.6 lb more feed per day than sows fed the control diet, but it did not result (P>0.10) in improvement in sow or piglet body weight (BW) at weaning. Sows fed the probiotic diet had marginally significant (P= 0.060) larger litter size after equalization on d 2 after birth, with on average 0.5 more piglet per litter than sows fed the control diet, but it did not result (P>0.10) in larger litter size at weaning. In the nursery, there was no evidence for effect of sow treatment, nursery treatment, or interactions (P>0.10) on overall growth performance. However, growth performance from d 21 to 42 and final nursery BW were greater (P<0.05) in pigs from sows fed the control diet compared to the probiotic diet. The evaluation of fecal score in nursing and nursery pigs indicated that fecal consistency was not influenced (P>0.10) by sow or pig diet. Microbial analysis revealed an increase (P<0.01) in number ofBacillus subtilisC-3102 and, consequently, totalBacillussp. in fecal microflora of sows and nursery pigs fed the probiotic diet. Also, piglets that were born and nursed by sows fed a probiotic diet also displayed this change (P<0.01) in fecal microbial population before weaning. In conclusion, the findings of this study demonstrate a potential benefit of providingBacillus subtilisC-3102 to sows during gestation and lactation on lactation feed intake. However, the probiotic inclusion to sow diets impaired growth performance and BW of the progeny in late nursery. The probiotic diet provided to sows or nursery pigs did not influence fecal consistency or number of potentially harmful bacteria in fecal microflora of sows and pigs. However, the probiotic diet was able to induce a change in fecal microbial population in sows, nursing piglets, and nursery pigs by increasing the number of totalBacillussp. The effects ofBacillus subtilisC-3102 on litter size after equalization require further elucidation in studies with larger number of sows and litters.
Keywords: Bacillus subtilis; Calsporin®; diarrhea; fecal consistency; nursery